An Ignored Fragment about the Stauroproskynesis on the Third Sunday of Lent. Euthymius Malakes’s On the Veneration of the Cross - Cuijpers, Mathieu (Analecta Bollandiana, 2024)
Cet article présente une édition critique du De adoratione sanctae Cru-cis d’Euthyme Malakès visant à remplacer le texte obsolète et défectueux d’Allatius. Sur la base de divers arguments, on s’attache à démontrer que ce texte a été écrit par Malakès, son authenticité étant attestée par les manuscrits, corroborée par des parallèles verbaux avec d’autres écrits de l’auteur, et acceptée par de nombreux spé-cialistes. Ce texte n’est par ailleurs qu’un fragment d’une homélie plus importante liée à la liturgie de la Stauroproskynesis, s’inspirant largement d’auteurs plus anciens et utilisant des thèmes et des images qui connaîtront une fortune durable dans la lit-térature religieuse des époques tardo- et post-byzantine. This article presents a critical edition of the De adoratione sanctae Crucis by Euthymius Malakes to replace the obsolete and defective text by Allatius. Based on a variety of arguments, the aim is to demonstrate that this text was written by Malakes, its authenticity being attested by the manuscripts, corroborated by verbal parallels with other writings by the same author, and accepted by numerous special-ists. Moreover, this text is only a fragment of a larger homily linked to the liturgy of the Stauroproskynesis, largely inspired by older authors and using themes and images that were to have a lasting influence on the religious literature of the late Byzantine and post-Byzantine periods.